DEFINITION AND ANALYSIS OF MOTION ACTIVITY AFTER-STROKE PATIENT FROM THE VIDEO STREAM - M. Yu. Katayev; N. G. Katayeva; S. G. Katayev; M. O. Abramov; V. A. Chistyakova (Бюллетень сибирской медицины)
This article describes an approach to the assessment of motion activity of man in after-stroke period, allowing the doctor to get new information to give a more informed recommendations on rehabilitation treatment than in traditional approaches. Consider description of the hardware-software complex for determination and analysis of motion activity after-stroke patient for the video stream. The article provides a description of the complex, its algorithmic filling and the results of the work on the example of processing of the actual data. The algorithms and technology to significantly accelerate the gait analysis and improve the quality of diagnostics post-stroke patients.